Pharmacological mechanisms underlying gastroprotective activities of the fractions obtained from Polygonum minus in Sprague Dawley rats - Abdulla, M.A.; Qader, S.W.; Lee, S.C.; Mohd Sirat, H.; Hamdan, S. (MDPI, 2012)
The leaves of Polygonum minus were fractionated using an eluting solvent to evaluate the pharmacological mechanisms underlying the anti-ulcerogenic activity of P. minus. Different P. minus fractions were obtained and evaluated for their ulcer preventing capabilities using the ethanol induction method. In this study, Sprague Dawley rats weighing 150–200 g were used. Different parameters were estimated to identify the active fraction underlying the mechanism of the gastroprotective action of P. minus: the gastric mucus barrier, as well as superoxide dismutase, total hexosamine, and prostaglandin synthesis. Amongst the five fractions from the ethanolic extract of P. minus, the ethyl acetate:methanol 1:1 v/v fraction (F2) significantly (p < 0.005) exhibited better inhibition of ulcer lesions in a dose-dependent manner. In addition, rats pre-treated with F2 showed a significant elevation in superoxide dismutase (SOD), hexosamine and PGE2 levels in the stomach wall mucosa in a dose-dependent matter. Based on these results, the ethyl acetate:methanol 1:1 v/v fraction was considered to be the best fraction for mucous protection in the ethanol induction model. The mechanisms underlying this protection were attributed to the synthesis of antioxidants and PGE2.